Oxford international lower secondary: English workbook 1 for grade 6 - Barber, Alison; Redford, Rachel (Karachi : Oxford university press, 2023)
This edition of Oxford International Lower Secondary English gives students the skills they need to become confident communicators with a strong grasp of English language, vocabulary and grammar. Students discover the joy of learning through speaking and listening, reading extracts from around the world, writing and performing. An enquiry-based approach encourages learner agency and active collaboration Students explore global themes, asking big questions and making connections Comprehension questions are categorized A (retrieval), B (language techniques) and C (inference) to allow for differentiation Language tips explain key grammar points and word origins boxes help make links across languages and build vocabulary Comprehensive Teacher$1 (Bs Guides support the Student Books with lesson guidance and additional ideas for teachings
Keywords: English - workbook